Evaluation of Creatine Kinase, Lactate Dehydrogenase, and Amylase Concentrations in Umbilical Blood of Preterm Infants after Long-Term Tocolysis - Yoshiyuki Nakajima; Naoki Masaoka (Hindawi Limited, 2014)
Creatine kinase (CK), lactate dehydrogenase (LDH), and amylase levels of preterm infants following long-term tocolysis in pregnant women are limited. The objective of this study was to determine if the tocolytic therapy affects CK, LDH, and amylase levels in the umbilical blood. This study included 215 preterm infants born to women treated with and without ritodrine hydrochloride. CK, LDH, and amylase levels in the umbilical blood at delivery were determined. Infants were divided according to the ritodrine tocolysis, as follows: Group A (n=91), not exposed to ritodrine; Group B (n=44), IV ritodrine for <1 week; Group C (n=80), IV ritodrine for ≥1 week. The CK concentration in cord blood of Group C (198.8±14.2 IU/L) was significantly higher in comparison with Group A (155.0±7.3 IU/L, P<0.05). There was no significant difference in LDH and amylase levels in the three groups. The CK significantly correlated with gestational age (r=0.42, P<0.01) and birth weight (r=0.38, P<0.01). LDH and amylase levels did not change with gestational age nor birth weight. In conclusion, long-term ritodrine tocolysis leads to increased umbilical blood CK level.